Analysis of Some Bottled Drinking Water Samples Available in Alkoms City (مجلة البحوث الأكاديمية, 2021)
Commonly consumed six local brands of bottled drinking water from Alkoms city were analysed. The acquired results were compared with both Libyan and WHO standards. Various physical and chemical properties were studied: pH, conductivity, and levels of Na, K, Ca, Mg. Conductivity and pH values of the tested samples were agreed with both Libyan and WHO limits. Na, K, Mg levels were in the acceptable range comparing with both Libyan and WHO limits, whereas calcium levels were up to four times as high as Libyan and WHO limits.
Keywords: Bottled Water; WHO,; pH,; Conductivity